Analisis Kesulitan Belajar Membaca dan Menulis Permulaan PAUD Di Kelompok Bermain Fun Islamic School - azis, muhammad (Universitas Islam Negeri Raden Intan Lampung, 2019)
Child learning difficulties are children who are disrupted in one o more basic psychological processes that include understanding and using spoken or written language. This study aims to describe the learning difficulties experienced by children aged 5-6 years in group playing FUN ISLAMIC SCHOOL Purworejo Yogyakarta. The method used is a qualitative research method with a case study approach. The data source consisted of 2 teachers in the group of children aged 5-6 years, and 4 children who had problems due to learning difficulties were the case subjects in this study. After data is collected, data is presented for inclusion. Reading difficulties in children aged 5-6 years are different, in the pocess of writing in class children have poor writing in learning activities in class. Based on the results of the study there are a number of suggestions that can be considered by related parties in an effort to overcome the learning difficulties of children.